Harmonizing Generational Gaps: Effective Strategies For Managing Generational Gaps In Professional Event Organizers (PT. Dyandra Promosindo) - Mbura, Helend A; Nurbaeti, Nurbaeti; Muhardiansyah , Doni (Advances In Social Humanities Research, 2025)
This research focuses on harmonizing generational gaps in the workplace environment at PT Dyandra Promosindo, a professional exhibition organizer in Indonesia. Thegenerational differences among employees, including Generation X, Y, and Z, present challenges related to collaboration, communication, and employee performance. The purpose of this study is to analyze the impact of generational gaps on team dynamics and identify effective strategies to enhance intergenerational interaction. The research employs a qualitative approach, collecting data through observations and interviews with employees at PT Dyandra Promosindo. The findings indicate that generational gaps influence employees' perceptions, values, and communication styles, which can potentially lead to conflicts and misalignment in teamwork. The recommended strategies include cross-generational communication training, cross-mentoring programs, and the implementation of flexible policies to foster better intergenerational integration. The implementation of these strategies is expected to create an inclusive work environment,improve productivity, and support harmonious collaboration within the company. This research contributes to the development of a more adaptive and responsive human resource management approach to generational diversity in the workplace.